Russian generals of the VXIIIi century: social dynamics generations - Feofanov Aleksandr (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2011)
In the present article the quantity and social structure of Russian generalship of the XVIIIth century is to be analysed. The main task is to consider the generational evolution, social origin and levels of education of generals of Russian Empire. Increase in the total number of generals is connected with reduction of the proportion of foreigners and with increase of the percentage of non-highborn nobility. Non-nobility for the entire studied period occurs here only as an exception. Proportion of people with «regular» education was low, but gradually increased. The groups combined on the basis of proximity of two main criteria: the time of birth and time of entry into service constitute generations. Generation means the community of people united in the sociocultural context, in this research we will concentrate on the initial conditions of socialization (social origin, education). The ﬁ rst generation began service in the XVIIth century and at the beginning of the reign of Peter I, and received general’s oﬃces in the same reign. Generals of the second generation got position of generals only at the beginning of the next period of Russian history - the era of palace revolutions. The third generation came into service in the era of palace revolutions, and reached general’s rank in the same period, or during the reign of Catherine II. Small amount entered into service after 1762, and received grades 1-2 class at the time of Paul I. In the ﬁrst generation one can consider the greatest number of representatives of the higher ranks of the Moscow state serving nobility. In the second generation there are some children of Peter’s generals (more than half of the composition) also closely associated with the old Moscow aristocracy. In the third generation the proportion of those whose fathers had the rank of general, is also slightly more than half. Since the reign of Catherine II, representatives of small and medium service nobility began to receive the generals’ position of ﬁrst two higher ranks in mass. Elite that was established during the modernization of Peter the Great, was based on meritocratic principles, and it was genetically related to the old Moscow nobility. For those who did not belong by birth to the serving elite a military education was a jumping-oﬀ place for a career.